2017
DOI: 10.1186/s12955-017-0631-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparing five depression measures in depressed Chinese patients using item response theory: an examination of item properties, measurement precision and score comparability

Abstract: BackgroundItem response theory (IRT) has been increasingly applied to patient-reported outcome (PRO) measures. The purpose of this study is to apply IRT to examine item properties (discrimination and severity of depressive symptoms), measurement precision and score comparability across five depression measures, which is the first study of its kind in the Chinese context.MethodsA clinical sample of 207 Hong Kong Chinese outpatients was recruited. Data analyses were performed including classical item analysis, I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 63 publications
(60 reference statements)
2
14
0
1
Order By: Relevance
“…These results corroborate data about precarious health conditions of quilombola population (Gomes et al, 2013;Oliveira, Pereira, Guimarães, & Caldeira, 2015), the need to establish mental health policies that consider this vulnerability, and to consider the characteristics of the sample when assessing the psychometric qualities of the instruments (Meredith & Teresi, 2006). They also show the usefulness of using screening instruments to identify depressive symptoms in poor areas (Zhao et al, 2017).…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…These results corroborate data about precarious health conditions of quilombola population (Gomes et al, 2013;Oliveira, Pereira, Guimarães, & Caldeira, 2015), the need to establish mental health policies that consider this vulnerability, and to consider the characteristics of the sample when assessing the psychometric qualities of the instruments (Meredith & Teresi, 2006). They also show the usefulness of using screening instruments to identify depressive symptoms in poor areas (Zhao et al, 2017).…”
Section: Discussionsupporting
confidence: 79%
“…In this study they observed a specificity ranging from .73, when adopting 7 as cut-off point, to .96, when adopting 15 as cut-off point. Other studies have also shown that the PHQ-9 has good discrimination capability for depressive disorders (Adler et al, 2012;Kendel et al, 2010;Zhao et al, 2017). Using this cut-off point, the PHQ-9 screened depression in a number of people twice higher than the depression prevalence estimated for the Brazilian general population (WHO, 2017).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…These studies do not, however, discuss the instrument's information in different score categories. More recently, Zhao, Chan, and Lo (2017) found that the Depression subscale is sufficiently informative only in the moderate and extremely severe categories.…”
mentioning
confidence: 99%